THE IMPLICATIONS OF BREXIT FOR THE EU’S SECURITY AND DEFENCE ACTORNESS IN THE WORLD - Münevver Cebecı (Ankara Avrupa Çalışmaları Dergisi)
This article aims to elucidate the implications of Brexit for the EU’s security and defence actorness. Building on Bretherton and Vogler’s conception of “global actorness”, it inquires first, into political and security implications, and, second, into defence implications. It argues that Brexit affects the EU’s security and defence actorness negatively in terms of its presence (its diplomatic weight and representation) whereas the impact on the Union’s defence capabilities might not be detrimental in the long run, despite the loss a Member State with significant military power.